Modern weapons and military equipment for issue 1/2014 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Unmanned air transport mules from IsraelSensor monitoring of land areaSatellite telescope Moiraorbital weapons "cosmic dome"Automat for frogmen from TulaHeckler & Koch HK XM25, smart grenade launcher